2016
DOI: 10.1371/journal.pone.0154476
|View full text |Cite
|
Sign up to set email alerts
|

The Path towards Endangered Species: Prehistoric Fisheries in Southeastern Brazil

Abstract: Brazilian shellmounds are archaeological sites with a high concentration of marine faunal remains. There are more than 2000 sites along the coast of Brazil that range in age from 8,720 to 985 cal BP. Here, we studied the ichthyoarchaeological remains (i.e., cranial/postcranial bones, otoliths, and teeth, among others) at 13 shellmounds on the southern coast of the state of Rio de Janeiro, which are located in coastal landscapes, including a sandy plain with coastal lagoons, rocky islands, islets and rocky bays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 82 publications
(107 reference statements)
3
51
0
8
Order By: Relevance
“…For example, Kloker et al (2010) recorded 17 fish species from two sites on the south coast of Brazil (Santa Catarina state). In contrast, as part of a greater sampling effort, Lopes et al (2016) recorded 97 fish species in 13 sites located on the coast of Rio de Janeiro, and in this study, the study area corresponded to 68 middens distributed over 1,000 km of the southeast coast of Brazil.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…For example, Kloker et al (2010) recorded 17 fish species from two sites on the south coast of Brazil (Santa Catarina state). In contrast, as part of a greater sampling effort, Lopes et al (2016) recorded 97 fish species in 13 sites located on the coast of Rio de Janeiro, and in this study, the study area corresponded to 68 middens distributed over 1,000 km of the southeast coast of Brazil.…”
Section: Discussionmentioning
confidence: 65%
“…In using even greater effort than that undertaken by Lopes et al (2016), this study used data which came from different kinds of publications (scientific articles, books, thesis, dissertations, monographs, technical reports etc) encompassing 48 years of studies in the field. Therefore, the data compiled here came from a myriad of objectives and methodologies, for example, primary data which came from excavations were originated since superficial sampling till total material recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this coastline has supported human populations for at least 6,000 years, through fishing, hunting and harvesting of estuarine and marine environments (Bastos et al, 2015;Colonese et al, 2014;Gaspar, 1998;Lima et al, 2004). Recent studies have revealed that pre-Columbian populations of the Atlantic Forest coastal zone potentially overexploited key taxonomic groups, causing a population decline (Lopes et al, 2016), but the scale of this exploitation remains a matter of debate.…”
mentioning
confidence: 99%